The Silenced Women : Can Public Activism Stimulate Reporting of Violence against Women? - Sahay, Abhilasha (World Bank, Washington, DC, 2021)
Although violence against women is pervasive and can have severe adverse implications, it is considerably underreported. This paper examines whether public activism against such violence can stimulate disclosure of socially sensitive crimes such as rape and sexual assault. The analysis uses a quasi-experimental setting arising from an infamous gang rape incident that took place on a moving bus in Delhi in 2012. The incident sparked widespread protests demarcating a nationwide ‘social shock’. Exploiting regional variation in exposure to the shock, the analysis finds an increase of 27 percent in reported violence against women after the shock but no change in gender-neutral crimes such as murder, robbery and riots. Additional evidence -- generated from self-compiled high frequency crime data -- suggests that the increase can be attributed to a rise in reporting rather than an increase in occurrence.